EXTRA-PULMONARY THROMBOSIS IN PATIENTS WITH CORONAVIRUS-19 DISEASE; CASE SERIES AND REVIEW OF THE LITERATURE - Madiha Iqbal,; Sher Muhammad Sethi,; Sadaf Hanif, (Journal of Ayub Medical College Abbottabad, 2022)
Background: Coronavirus disease 19 (COVID-19) is a viral disease caused by SARS-CoV-2. There is an increased incidence of a thromboembolic phenomenon in patients with COVID-19 infection. Pulmonary embolism is the most common thrombotic presentation in COVID-19 patients. Extra-pulmonary thrombosis is an unusual thrombotic complication of COVID-19 disease. Methods: This study was conducted at The Aga Khan University Hospital from June-July'2021. Patients clinical and laboratory findings, treatment, and outcomes were recorded. Results: We report three cases with the diagnosis of COVID-19 pneumonia associated with extra-pulmonary thrombosis from June to July 2021. The mean age of the patients were 66.3 and two of them (66.6%) were male. The diagnosis of COVID-19 was confirmed by real-time reverse transcriptase-polymerase chain reaction analysis in all the three patients. Extra-pulmonary thrombosis was identified in the celiac artery and splenic veins in case 1, left common iliac artery in case 2, and left ventricular apical thrombus in case 3. All the patients were treated with anticoagulation. In total, two patients were discharged home after total recovery, while the third patient died. Conclusion: The take-home message is that COVID-19 infection is a pro-thrombotic condition that can provoke arterial and venous thrombosis. Extra-pulmonary thrombosis is increasingly identified with COVID-19 infection. It is important to remember that the patient might have no potential risk factor for thromboses, as COVID-19 infection per se is a risk to induce thrombosis.